Patient-Centered Approaches to Transitional Care Research and Implementation: Overview and Insights From Patient-Centered Outcomes Research Institute’s Transitional Care Portfolio - Parry, Carly (Med Care, 2021)
This Special Issue, Future Directions in Transitional Care Research, focuses on the approaches used and lessons learned by researchers conducting care transitions studies funded by the Patient-Centered Outcomes Research Institute (PCORI). PCORI’s approach to transitional care research augments prior research by encouraging researchers to focus on head-to-head comparisons of interventions, the use of patient-centered outcomes, and the engagement of stakeholders throughout the research process. OBJECTIVES: This paper introduces the themes and topics addressed by the articles that follow, which are focused on opportunities and challenges involved in conducting patient-centered clinical comparative effectiveness research in transitional care. It provides an overview of the state of the care transitions field, a description of PCORI’s programmatic objectives, highlights of the patient and stakeholder engagement activities that have taken place during the course of these studies, and a brief overview of PCORI’s Transitional Care Evidence to Action Network, a learning community designed to foster collaboration between investigators and their research teams and enhance the collective impact of this body of work. CONCLUSIONS: The papers in this Special Issue articulate challenges, lessons learned, and new directions for measurement, stakeholder engagement, implementation, and methodological and design approaches that reflect the complexity of transitional care comparative effectiveness research and seek to move the field toward a more holistic understanding of transitional care that integrates social needs and lifespan development into our approaches to improving care transitions.